Vagrant and Neglected Minors in Soviet Lithuania 1944–1954: The Problem and the Solutions - Balčiūnė, Ieva (Lietuvos istorijos studijos, 2021)
This article presents the analysis of how the issue of vagrant and neglected (“беспризорные и безнадзорные”) minors in Soviet Lithuania was dealt with during the period of 1944–1954. After the Soviet occupation of Lithuania in 1944, stencil measures of dealing with the issue were imposed. However, the problem of vagrant and neglected minors in postwar Lithuania was specific and had changed. Therefore, the research reveals the dynamics of the problem and, by taking into account the Soviet Lithuanian context, the measures taken to solve it. Up until the beginning of the 1950s, vagrant and neglected minors were mostly street children and orphans from WWII. A considerable part of them had migrated from Russian and Belarusian territories in search for food. The government’s aims were to reduce their numbers, move them from the streets and change their official status. But in the 1950s, the problem, as it was seen, had transformed to juvenile delinquency and required respective measures. The research discovers how the system of custody, imprisonment, accommodation and care of these minors worked in early Soviet Lithuania.